Bioenergetic Requirements and Spatiotemporal Profile of Nerve Growth Factor Induced PI3K-Akt Signaling Along Sensory Axons - Sainath, Rajiv; Gallo, Gianluca (Frontiers in Molecular Neuroscience, 2021)
Nerve Growth Factor (NGF) promotes the elaboration of axonal filopodia and branches through PI3K-Akt. NGF activates the TrkA receptor resulting in an initial transient high amplitude burst of PI3K-Akt signaling followed by a maintained lower steady state, hereafter referred to as initiation and steady state phases. Akt initially undergoes phosphorylation at T308 followed by phosphorylation at S473, resulting in maximal kinase activation. We report that during the initiation phase the localization of PI3K signaling, reported by visualizing microdomains of PIP3 formation, and Akt signaling, reflected by Akt phosphorylation at T308, correlates with the positioning of axonal mitochondria. Mitochondrial oxidative phosphorylation but not glycolysis is required for Akt phosphorylation at T308. In contrast, the phosphorylation of Akt at S473 is not spatially associated with mitochondria and is dependent on both oxidative phosphorylation and glycolysis. Under NGF steady state conditions, maintenance of phosphorylation at T308 shows dual dependence on oxidative phosphorylation and glycolysis. Phosphorylation at S473 is more dependent on glycolysis but also requires oxidative phosphorylation for maintenance over longer time periods. The data indicate that NGF induced PI3K-Akt signaling along axons is preferentially initiated at sites containing mitochondria, in a manner dependent on oxidative phosphorylation. Steady state signaling is discussed in the context of combined contributions by mitochondria and the possibility of glycolysis occurring in association with endocytosed signalosomes.